Design of Polarization-Maintaining FBGs Using Polyimide Films to Improve Strain-Temperature Sensing in CFRP Laminates - Andrea Annunziato; Francesco Anelli; James Gates; Christopher Holmes; Francesco Prudenzano (IEEE Photonics Journal)
Uniform Fiber Bragg Grating sensors based on Polarization-Maintaining fibers are designed for simultaneous longitudinal strain and temperature measurement of Carbon Fiber Reinforced Polymer laminates. Panda, Bow tie and Pseudo-rectangle optical fiber shape sections are investigated employing three different embedding methods, for each optical fiber. The simulation accurately takes into account that the fibers are embedded in unidirectional Carbon Fiber Reinforced Polymer and covered between two adhesive polyimide films. An exhaustive, accurate and robust investigation of the mechanisms originating Bragg wavelength shift is developed by considering a complete multiphysical model including: the propagation modes and their interaction, the birefringence, the optomechanical and thermal behaviour of both the optical fiber and the embedding composite material. For the first time, the use of polyimide films is proposed to obtain an increase of temperature sensor sensitivity, reducing the stress-transfer, due to thermal expansion, between the composite laminate and the sensing element. The designed Fiber Bragg Grating sensors are compared and their potential application, for simultaneous strain and temperature measurement of Carbon Fiber Reinforced Polymer is discussed.